2021
DOI: 10.20473/jkl.v13i2.2021.113-120
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Diarrhea in Toddlers with Open Defecation Free (ODF) Status in Tuban Regency

Abstract: Introduction: The Tuban Regency Health Profile in 2019 stated that the villages with ODF status had reached 64 villages (19.5%) out of 328 total villages, while the villages reported having implemented Community-Based Total Sanitation (CBTS) have reached 100%. The low ODF status achieved indicates that most people still defecate openly, which will increase health risks due to environmental pollution. This study aimed to determine the distribution map of diarrhea in toddlers in each district of Tuban Regency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…This was an ecological study with a crosssectional design supported by mapping (Laksono & Kusrini, 2020;Mahendra et al, 2021). The population in this study is all districts (31 districts) in Surabaya City, East Java province, so the unit of analysis is the district.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was an ecological study with a crosssectional design supported by mapping (Laksono & Kusrini, 2020;Mahendra et al, 2021). The population in this study is all districts (31 districts) in Surabaya City, East Java province, so the unit of analysis is the district.…”
Section: Methodsmentioning
confidence: 99%
“…Targeting diarrhea transmission hotspots was one potential strategy to reduce diarrhea cases. The spatial pattern of the percentage of children with persistent diarrhea was related to households with sanitation facilities (Mahendra et al, 2021).…”
Section: Mapping Of Priority Areas Interventions For Toddler Diarrheamentioning
confidence: 99%
“…In Indonesia after CLTS triggering, it was concluded that the sub-district with the lowest ODF status was at 28% in 2018 (Pertiwi et al, 2018). Only 19.5% of Indian homes had implemented CLTS at a 100% rate, according to a survey done in villages (Mahendra et al, 2021). Lack of adequate information and support for building latrines affected the full realization of this intervention.…”
Section: 68%mentioning
confidence: 99%
“…Several interventions have been employed to reduce diarrhea: Improvements in water, sanitation, and hygiene facilities; exclusive breastfeeding, adequate complementary feeding, and continued breastfeeding; Vitamin A supplementation; and a preventative rotavirus vaccine [1], [5], [6], [7]. There is strong evidence that flies are vectors of infectious diseases, especially diarrhea [8], [9].…”
Section: Introductionmentioning
confidence: 99%